Environmental management plan for the irrigation improvement project (IIP) - Tajan subproject - Namvargolian, Ramiz, author; Ayaz, G., author; Bichara, Adel, author; Bond, Andrew, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
The Irrigation Improvement Project (IIP) is funded jointly by the Government of Iran and the World Bank. The project with an estimated cost of US$ 312 million started in 1994 and is expected to be completed by end of2001. The project implements irrigation improvement measures in about 107,000 hectares in four subproject areas located in northern and southern Iran. Existing irrigation and associated agricultural practices are having environmental impacts on natural and important man-made ecosystems both within and downstream of each of the subprojects areas particularly on local and migratory wildlife. A major part of IIP is an Environmental Management Plan (EMP) which includes in part a) strengthening the institutions and training the personnel responsible for addressing long-term environmental issues related to irrigated agriculture, b) establishing agricultural chemicals management program and surface water and groundwater quality monitoring programs, and c) preparing special studies and mitigation plans to address long-term environmental management issues related to the development of irrigated agriculture. Good progress has been made with respect to the civil engineering works associated with the project, but a number of issues have delayed environmental mitigation activities associated with the project. Special environmental issues of IIP, particularly those associated with the Tajan Subproject and related mitigation actions are presented in this paper. The traditional irrigation in the Tajan subproject area on the Caspian coast of Iran has resulted in the creation of large irrigation water storage ponds locally known as "ab-bandan". Ab-bandans have evolved into complex man-made and man-maintained ecosystems which are highly valuable to local residents and to local and migratory wildlife. A plan of management for the complex ecosystems of Abbandans is being developed.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.